2013
DOI: 10.1111/jmft.12019
|View full text |Cite
|
Sign up to set email alerts
|

The Alliance in Relationship Education Programs

Abstract: Couple relationship education (CRE) programs are associated with positive romantic relationship outcomes; however, the mechanisms by which these gains occur are less understood. The current study (122 couples) utilized actor-partner modeling to examine the association between the therapeutic alliance and dedication and negative and positive communication for racial/ethnic minority couples. Additionally, we examined whether gender and delivery format moderated these relationships. Results demonstrated that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 61 publications
0
32
0
4
Order By: Relevance
“…For example, research has not examined the influence of specific CRE tools on relationship outcomes. The influence of participating in a group workshop format has only recently been examined (e.g., Quirk, Owen, Inch, France, & Bergen, 2013). Further, couples who participate and complete CRE typically demonstrate an intentional commitment to improve their relationship.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…For example, research has not examined the influence of specific CRE tools on relationship outcomes. The influence of participating in a group workshop format has only recently been examined (e.g., Quirk, Owen, Inch, France, & Bergen, 2013). Further, couples who participate and complete CRE typically demonstrate an intentional commitment to improve their relationship.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…The common factor research paradigm focuses on processes of change related to client, therapist, or relationship characteristics. For example, substantial support has emerged for the importance of the therapeutic alliance in couple interventions from a meta‐analysis (Friedlander, Escudero, Heatherington, & Diamond, ) as well as studies on therapy (e.g., Anker, Owen, Duncan, & Sparks, ; Knobloch‐Fedders, Pinsof, & Mann, ) and relationship education programs (e.g., Quirk, Owen, Inch, France, & Bergen, ).…”
Section: Change In Spouse Behavior During Traditional and Integrativementioning
confidence: 99%
“…Quirk et al. (), whose sample characteristics were closest to those in the current study, found large actor effects of the facilitation alliance on negative communication and small actor effects on positive communication, relationship confidence and dedication for both men and women. Additionally, men's stronger alliance was related to their partner's improved communication and confidence/dedication, suggesting that there are systemic effects between partners.…”
Section: Facilitation Alliancementioning
confidence: 99%
“…Notably, recent findings suggest that efforts to maximize the efficacy of CRE programs may also need to evaluate this overlooked asset—the CRE facilitation alliance. Two recent studies examining effects of the facilitation alliance found that key relationship outcomes from pre‐ to posttest varied based on the level of the alliance between facilitator and participant (Owen, Rhoades, Stanley, & Markman, ; Quirk, Owen, Inch, France, & Bergen, ). The current study seeks to expand the literature examining the association between the facilitation alliance and relationship outcomes for a diverse group of couples participating in CRE.…”
mentioning
confidence: 99%